2014
DOI: 10.1111/rda.12364
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Field Based Chromatin Dispersion Assay to Assess Sperm DNA Fragmentation in the Bottlenose Dolphin (Tursiops truncatus)

Abstract: Over the last two decades, there have been significant advances in the use of assisted reproductive technology for genetic and reproductive management of captive dolphin populations, including evaluation of sperm DNA quality. This study validated a customized sperm chromatin dispersion test (SCDt) for the bottlenose dolphin (Tursiops truncatus) as a means of assessing sperm DNA damage both in the field and in the laboratory. After performing the SCDt, two different sperm morphotypes were identified: (i) sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Recently, we have conducted a validation experiment on DNA fragmentation of dolphin spermatozoa from multiple ejaculates of frozen–thawed semen based one individual and found a high correlation between the two‐tail comet assay and SCDt (Sánchez‐Calabuig et al. ); this work revealed that the SCDt, with minor modifications to the standard protocol, can be readily performed in the field as in the laboratory.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Recently, we have conducted a validation experiment on DNA fragmentation of dolphin spermatozoa from multiple ejaculates of frozen–thawed semen based one individual and found a high correlation between the two‐tail comet assay and SCDt (Sánchez‐Calabuig et al. ); this work revealed that the SCDt, with minor modifications to the standard protocol, can be readily performed in the field as in the laboratory.…”
Section: Introductionmentioning
confidence: 80%
“…Indeed, the SCDt is the only technique to date that has been specifically customized and validated for dolphin spermatozoa in terms of protein lysis for assessing damaged DNA; the SCDt can also be conducted in a standard andrology laboratory or in the field (Sánchez‐Calabuig et al. ). In fact, it is very important to standardize all sperm evaluation techniques, especially for wildlife species, as access to these animals is limited and samples obtained are highly valuable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations